Paul Mattick: Selected Texts - Roth, Gary, (Historical Materialism Book Series ;, 2025)
These essays by Paul Mattick were written during periods of radical activity and address themes still critical for us today-the devastation of war-torn areas and the abject destitution to which beleaguered populations are subjected, the authoritarian character of ostensibly democratic regimes, the ecological disasters that increasingly beset the world, the rationale behind and limits to governmental efforts to stimulate and stabilize the economy, and Mattick's assessment of economic theorizing within the marxian tradition. The essays combine contemporary commentary with theoretical analysis and represent some of the finest work Mattick produced. See Less